Accounting Analysis Of Product Life Cycle Costs Directed At Continuous Improvement And Its Role In Reducing Costs Applied Research In Nasr General Company For Mechanical Industries - Nabeel Farhan Hamdan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The product life cycle was first used in US Department of Defense military matters, where it applied mainly to DoD procurement of military equipment. Its use has expanded by companies operating in various sectors, such as building and construction, machinery and equipment manufacturing, and other industries that require high costs, and the life cycle of their products is relatively long and has clear stages, as the complete product life cycle mainly covers the costs of research, experimentation, acquisition, maintenance, transportation, and storage, and that the essence LCC is not only the running cost, but also the cost related to the product.The research at Nasr General Company for Mechanical Industries aims to shed light on two main tools of contemporary cost management that work to calculate the cost of the product over the product life cycle and make improvements to it continuously according to the continuous improvement technique. Thus, they work appropriately to reduce product costs and the costs are calculated according to The accounting system prepared in the company under investigation..